Molecular phylogeny of Cytospora species associated with canker diseases of fruit and nut crops in California, with the descriptions of ten new species and one new combination - Daniel P. Lawrence; Leslie A. Holland; Mohamed T. Nouri; Renaud Travadon; Ara Abramians; Themis J. Michailides; Florent P. Trouillas (IMA Fungus)
Abstract Cytospora species are destructive canker and dieback pathogens of woody hosts in natural and agroecosystems around the world. In this genus, molecular identification has been limited due to the paucity of multi-locus sequence typing studies and the lack of sequence data from type specimens in public repositories, stalling robust phylogenetic reconstructions. In most cases a morphological species concept could not be applied due to the plasticity of characters and significant overlap of morphological features such as spore dimensions and fruiting body characters. In this study, we employed a molecular phylogenetic framework with the inclusion of four nuclear loci (ITS, translation elongation factor 1-alpha, actin, and beta-tubulin) to unveil the biodiversity and taxonomy of this understudied important genus of plant pathogens. Phylogenetic inferences based on 150 Californian isolates revealed 15 Cytospora species associated with branch and twig cankers and dieback of almond, apricot, cherry, cottonwood, olive, peach, pistachio, plum, pomegranate, and walnut trees in California. Of the 15 species recovered in this study, 10 are newly described and typified, in addition to one new combination. The pathogenic status of the newly described Cytospora species requires further investigation as most species were associated with severe dieback and decline of diverse and economically important fruit and nut crops in California.